(untitled) - Ishikawa, Kaoru (Englewood Cliffs, 1985)
Describes the Japanese approach to quality control, explains how quality circles work, and discusses applications in subcontracting and marketing.
Keywords: Kiểm soát chất lượng,Quality control; Nhật Bản,Japan